STRONGYLOIDOSIS PADA ANAK BABI PRA-SAPIH - Oka, Ida Bagus Made; Dwinata, I Made (Buletin Veteriner Udayana; Vol. 3 No.2 Agustus 2011)
The Research was conducted to determine the contribution Strongyloides ransomi againstdiarrhea in piglets on pig farms inBali. The number of sample 501 piglets feces fromBadung, Tabanan and Gianyar. The examination of worm eggs with Sodium AceticFoemaldehid method (SAF). The data obtained were analyzed statistically with Fischer test/ Chi Qwadrat Test.The results was obtained the prevalence of Strongyloides ransomi in piglets of 7.4%. Theresults was found a significant relationship between infection Strongyloides ransomi withdiarrhea, where the infected piglets Strongyloides ransomi higher risk ( OR=6 ) than ofpiglets uninfected.
Keywords: Strongyloides ransomi, piglets